From Envisioning to Designing e-Development : The Experience of Sri Lanka - Hanna, Nagy K. (Washington, DC : World Bank, 2012)
This book focuses on identifying the potential benefits of a holistic, cross-sectoral development driven approach to Information and Communication Technology (ICT) and how it relates to economic development and competitiveness for Sri Lanka. This volume, the first of two about moving e-Sri Lanka from vision to implementation, focuses on the design of the strategy aimed at enabling Sri Lanka to join the global information services economy. The volume first provides an overview of why and how the e-Sri Lanka strategy was designed, the nature of this strategy, and how World Bank funding was secured. It then looks at the potential of the software and information services sector and at the mechanisms to develop the human resources and local and export markets for a thriving sector. Finally, it examines why and how to extend affordable information infrastructure to all, particularly those in the country's rural and impoverished areas.